1993
DOI: 10.1021/bi00069a003
|View full text |Cite
|
Sign up to set email alerts
|

A structural domain (the lid) found in pancreatic lipases is absent in the guinea pig (phospho)lipase

Abstract: Typically pancreatic lipases are characterized by the following properties: (1) they are activated by lipid/water interfaces (interfacial activation), (2) they are inhibited by bile salts but reactivated by colipase (a small activator protein), and (3) they do not hydrolyze significantly phospholipids. A cDNA clone encoding a guinea pig pancreatic (phospho)lipase (GPL) has been sequenced and expressed. The enzyme (recombinant as well as native) differs from other pancreatic lipases in that (1) it is not interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
136
1
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(142 citation statements)
references
References 33 publications
0
136
1
5
Order By: Relevance
“…In this report we describe the characterization of one of them, nmd, encoding an unknown member of the enzyme family of lipases. The predicted NMD polypeptide lacks a so-called 'lid' domain, as was earlier described for guinea pig pancreatic (phospho)lipase GPLRP2 and the phospholipase Al from hornet venom (Dolml) [5,6].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…In this report we describe the characterization of one of them, nmd, encoding an unknown member of the enzyme family of lipases. The predicted NMD polypeptide lacks a so-called 'lid' domain, as was earlier described for guinea pig pancreatic (phospho)lipase GPLRP2 and the phospholipase Al from hornet venom (Dolml) [5,6].…”
Section: Introductionmentioning
confidence: 85%
“…Sequence analysis revealed that nmd is a novel gene encoding a 50 kDa protein, which probably represents a new member of the enzyme family of lipases [5,18,19]. The similarity with other lipases is sufficiently high to classify NMD as an a/ (3-hydrolase-fold enzyme [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a consequence of the phenomenon called interfacial activation 17 . In most cases, the active site of the lipase is covered by short amphiphathic α-helix called the lid (closed form) make it inaccessible in the medium 18 .…”
Section: Introductionmentioning
confidence: 99%